Pengelolaan Persediaan Bahan Baku Simplisia di PT Lawu Flora Wijaya Karanganyar - Rahma Bayu Citra Aditama; R. Hermawan; Endah Puspitojati (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2024)
Raw material inventory management determines the company's impressive steps that affect the company's financial stability. The research aims to determine the efficient amount of ordering raw materials total inventory costs before and after using the Economic Order Quantity (EOQ) method, Re-Order point, and buffer inventory (Safety Stock) on Simplicia spoon, mint, and stevia. The research was carried out from January to June 2023 at PT Lawu Flora Wijaya, Karanganyar Regency. The method used in the research is a quantitative descriptive method. Based on research results using 2022 data, PT Lawu Flora Wijaya has been efficient in ordering 261.05 kg of Simplicia spoon raw materials, 104.74 kg of mint Simplicia, 84.64 kg of stevia Simplicia. The total cost of raw material inventory for Simplicia before using EOQ is Rp. 409,234 for spoon simplicia, Rp. 214,026 for mint simplicia, and Rp. 145,471 for stevia simplicia. Meanwhile, using the EOQ method, Rp. 402,171 was obtained for spoon simplicia, Rp. 189,937 for mint simplicia, and Rp. 144,609 for stevia simplicia. The reorder point for the raw material Simplicia spoon was 142.9 kg, simplicia mint was 15.1 kg, and Simplicia stevia was 25 kg. The buffer stock for spoon simplicia is 126.72 kg, mint simplicia is 11.92 kg, and stevia simplicia is 22.92 kg.